2022
DOI: 10.1186/s12884-022-04789-7
|View full text |Cite
|
Sign up to set email alerts
|

Receiving screened donor human milk for their infant supports parental wellbeing: a mixed-methods study

Abstract: Background Access to donor human milk (DHM) has primarily been based on the health and development outcomes of premature infants but there has been little examination of the broader impact of an infant receiving it upon parental mental health. Breastfeeding and mental health are closely tied with women who experience breastfeeding difficulties or are unable to meet their own breastfeeding goals often experiencing feelings of guilt, sadness and anger, alongside an increased risk of postnatal dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Randomised control trials in India ( 5), along with observational findings from the USA (6,8,9), India (21) and Europe (7,22), published since this systematic review have confirmed that when used in the context of optimal lactation support, DHM can be additionally supportive of lactation. This consistent finding could be explained in part by the psychological stressor of trying to avoid formula use and with the widely known risks of increased NEC and other complications of prematurity, which may impact negatively on the physiological ability of mothers to establish lactation (7,23,24). Secondary lactogenesis depends on an increase in prolactin and oxytocin, mediated by the hypothalamic-pituitary axis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Randomised control trials in India ( 5), along with observational findings from the USA (6,8,9), India (21) and Europe (7,22), published since this systematic review have confirmed that when used in the context of optimal lactation support, DHM can be additionally supportive of lactation. This consistent finding could be explained in part by the psychological stressor of trying to avoid formula use and with the widely known risks of increased NEC and other complications of prematurity, which may impact negatively on the physiological ability of mothers to establish lactation (7,23,24). Secondary lactogenesis depends on an increase in prolactin and oxytocin, mediated by the hypothalamic-pituitary axis.…”
Section: Discussionmentioning
confidence: 89%
“…A limited qualitative study from the US with 35 participants highlighted that women felt DHM offered a bridge to breastfeeding, allowing time to overcome short term hurdles, while the introduction of infant formula compounded their feelings of personal failure (26). In a recent sample of 105 parents whose infants have received DHM within the last year, responses suggest increased parental wellbeing (7), though further studies are needed to understand how widely these perceptions may be in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While trauma has been identified among parents whose children experience life‐threatening illness (Foster et al, 2017; Mortensen et al, 2015; Muscara et al, 2015; Woolf et al, 2016), the effects of trauma on breastfeeding in paediatrics are unstudied. The identified challenges of expressing milk may justify the extension of donor human milk provision in the paediatric setting to augment a mother's efforts to keep her child exclusively breastmilk fed, which has been shown to promote parental mental health (Brown & Shenker, 2022).…”
Section: Discussionmentioning
confidence: 99%